2010
DOI: 10.3111/13696991003723023
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and outcomes associated with copayment burden in schizophrenia: a cross-sectional survey

Abstract: Patient data were self-reported, which may have introduced additional bias in the study measures. Also, the use of a cross-sectional design precludes causal inference and the use of the current sampling methodology (both interview and Internet panel) might impact the ability to generalize the results to the broader population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Patient access to health care services (affected by geographic location, transportation difficulties, and cultural or language issues) may influence patient adherence to antipsychotic therapy 8. Patients with schizophrenia are frequently unemployed and/or in poverty,30,31 which may contribute to nonadherence caused by the financial burden of medication (eg, medication copayments) 30,32. Even small increases in insurance copayments have been associated with declining adherence and corresponding increases in psychiatric hospital admissions 32.…”
Section: Resultsmentioning
confidence: 99%
“…Patient access to health care services (affected by geographic location, transportation difficulties, and cultural or language issues) may influence patient adherence to antipsychotic therapy 8. Patients with schizophrenia are frequently unemployed and/or in poverty,30,31 which may contribute to nonadherence caused by the financial burden of medication (eg, medication copayments) 30,32. Even small increases in insurance copayments have been associated with declining adherence and corresponding increases in psychiatric hospital admissions 32.…”
Section: Resultsmentioning
confidence: 99%
“…This original survey, conducted between December 2007 and February 2008, was initiated to understand the treatments, attitudes, health behaviors, and health outcomes among patients with schizophrenia. The data generated from this survey has been used in several previous studies, each of which has outlined the methods in some detail [4,19]. Briefly, patients were convenience sampled in one of two ways to participate in a self-administered survey to create the dataset: (1) patients who reported having schizophrenia in an Internet-based consumer panel (Lightspeed Research Ailment Panel) were randomly sent an invitation to participate in a web-based questionnaire via email, and (2) patients were also recruited from grassroots campaigns and newspaper advertising to arrive at a central interview facility to take a paper copy of the survey instrument.…”
Section: Methodsmentioning
confidence: 99%
“…For this study we used a threshold of one or more items to identify nonadherence; adherence was classified as reporting "no" for all items. This approach has been reported in previous schizophrenia research [19]. …”
Section: Methodsmentioning
confidence: 99%
“…A study in the USA found that higher patient cost-sharing (eg, copayments or coinsurance) was associated with a lower likelihood of adherence with antipsychotic medication and a shorter time to discontinuation of medication 58. In another study, schizophrenia patients who perceived copayment burden were less than half as likely to have complete adherence 59. This result needs to be considered in light of the study’s methodological weaknesses that included a cross-sectional design and use of self-reported patient data.…”
Section: Factors Associated With Nonadherencementioning
confidence: 97%